2019
DOI: 10.36740/wlek201904129
|View full text |Cite
|
Sign up to set email alerts
|

The Level of Some Hormones in the Blood Women With Endometriosis Which Associated With Infertility

Abstract: Introduction: The work has been dedicated the study of pituitary hormone concentration in the blood of women with endometriosis-associated infertility on 2-3 days of the menstrual cycle and the day of the puncture of ovarian stimulation superovulation in the cycle. The aim of our study was to examine the concentration of pituitary hormones in the blood of women with endometriosis associated with infertility. Materials and methods: For the purpose of the research we have conducted a special study of protein (lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…As well, in low-responder in vitro fertilization (IVF) individuals, gonadotropin therapy had increased follicular response. This perspective leads to higher levels of gonadotropin and increased follicular response compared to the mini-dose GnRH agonist protocol [45]. Few other research studies had reported that after 21 days of unintended chronic stress in adult male rats, reduced body weight, serum testosterone levels, and genital index were observed [37].…”
Section: Testosteronementioning
confidence: 99%
“…As well, in low-responder in vitro fertilization (IVF) individuals, gonadotropin therapy had increased follicular response. This perspective leads to higher levels of gonadotropin and increased follicular response compared to the mini-dose GnRH agonist protocol [45]. Few other research studies had reported that after 21 days of unintended chronic stress in adult male rats, reduced body weight, serum testosterone levels, and genital index were observed [37].…”
Section: Testosteronementioning
confidence: 99%
“…In the United Kingdom, around half of women commence pregnancy overweight or obese (Euro‐Peristat Project, 2018), with the United Kingdom having the highest rates of maternal obesity in Europe (Devlieger et al, 2016). Women who are obese (with a body mass index [BMI] of 30 or over) are at a greater risk of complications in the antenatal, intrapartum and postnatal periods (Bakun, Karatieieva, Semenenko, Yurkiv, & Berbets, 2018), and excess gestational weight gain is associated with postnatal weight retention (Begum, Colman, McCargar, & al., 2012; Endres et al, 2015) and longer term adverse maternal health effects (Valgeirsdottir et al, 2019).…”
Section: Introductionmentioning
confidence: 99%